Human Serum Enhances Biomimicry of Engineered Tissue Models of Bone and Cancer - Villasante, Aranzazu; Robinson, Samuel T.; Cohen, Andrew R.; Lock, Roberta; Guo, X. Edward; Vunjak-Novakovic, Gordana (Frontiers in Bioengineering and Biotechnology, 2021)
For decades, fetal bovine serum (FBS) has been used routinely for culturing many cell types, based on its empirically demonstrated effects on cell growth, and the lack of suitable non-xenogeneic alternatives. The FBS-based culture media do not represent the human physiological conditions, and can compromise biomimicry of preclinical models. To recapitulate in vitro the features of human bone and bone cancer, we investigated the effects of human serum and human platelet lysate on modelling osteogenesis, osteoclastogenesis, and bone cancer in two-dimensional (2D) and three-dimensional (3D) settings. For monitoring tumor growth within tissue-engineered bone in a non-destructive fashion, we generated cancer cell lines expressing and secreting luciferase. Culture media containing human serum enhanced osteogenesis and osteoclasts differentiation, and provided a more realistic in vitro mimic of human cancer cell proliferation. When human serum was used for building 3D engineered bone, the tissue recapitulated bone homeostasis and response to bisphosphonates observed in native bone. We found disparities in cell behaviour and drug responses between the metastatic and primary cancer cells cultured in the bone niche, with the effectiveness of bisphosphonates observed only in metastatic models. Overall, these data support the utility of human serum for bioengineering of bone and bone cancers.